Decision Making about Risk of Infection by Young Adults with CF - Lisa Reynolds; Gary Latchford; Alistair J. A. Duff; Miles Denton; Tim Lee; Daniel Peckham (Pulmonary Medicine)
Young people with cystic fibrosis (CF) are asked to avoid a number of environments associated with increased infection risk, but in practice they need to balance this with competing priorities such as building and sustaining relationships with friends and family. This study explored the process by which young people make these decisions. Mixed methods were used: a vignette study presenting choices around engaging in activities involving a degree of infection risk and a thematic analysis of participant's accounts of their decision making. The eight participants chose to engage in high risk behaviours in 59% of the choices. All participants chose to engage in at least one risky behavior, though this was less likely when the risk was significant. Thematic analysis revealed large areas of misunderstanding and lack of knowledge, leading to some potentially worrying misconceptions about the nature of infections and risk. Young people with CF are not currently making informed decisions around activities that involve increased risk of infection, and there is an urgent need for CF teams to address this in information provision.